Influences on antimicrobial prescribing behaviour of veterinary practitioners in cattle practice in Ireland. (5th January 2013) - Gibbons, J. F.; Boland, F.; Buckley, J. F.; Butler, F.; Egan, J.; Fanning, S.; Markey, B. K.; Leonard, F. C.
Abstract : Guidelines on prudent antimicrobial use in veterinary medicine have been developed to reduce inappropriate prescribing of antimicrobials. Such guidelines focus mainly on the clinical and pharmacological indications for prescribing. A questionnaire study of veterinary surgeons engaged in cattle practice was completed to determine if non‐clinical issues influence the decision to prescribe antimicrobials, and to assess if pharmacological and non‐pharmacological issues influence the choice of antimicrobial prescribed. Non‐clinical issues, including issues related to professional stress, influenced the prescribing decision of the majority of respondents. However, the nature of the veterinarian–client relationship did not influence the prescribing behaviour of the majority of respondents. Pharmacological and non‐pharmacological issues influenced the choice of antimicrobial prescribed. The veterinary surgeon's prior experience of a drug was considered 'often' or 'always' by 95.7 per cent of respondents when making this decision. The findings of this study have implications for the recognition and management of stress within the profession, and for the development of intervention strategies to reduce inappropriate antimicrobial prescribing.